2021
DOI: 10.1093/eurheartj/ehab687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gene validity for CPVT and short QT syndrome in sudden arrhythmic death

Abstract: Aims Catecholaminergic polymorphic ventricular tachycardia (CPVT) and short QT syndrome (SQTS) are inherited arrhythmogenic disorders that can cause sudden death. Numerous genes have been reported to cause these conditions, but evidence supporting these gene–disease relationships varies considerably. To ensure appropriate utilization of genetic information for CPVT and SQTS patients, we applied an evidence-based reappraisal of previously reported genes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…With the increased use of genetic screening in families with a history of SCD, there is increasing evidence of the involvement of different genes in the development of CPVT. Recently, a panel of gene curation experts reviewed all published evidence for CPVT-associated genes curated by three independent genes, and identified five more genes with concrete evidence for their causation of CPVT, aside from RyR2 and CASQ2 [ 93 ]. RYR2, CALM1, CALM2, and CALM3 were inherited in an autosomal dominant inheritance, whilst CASQ2, TRDN, and TECRL had an autosomal recessive inheritance [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the increased use of genetic screening in families with a history of SCD, there is increasing evidence of the involvement of different genes in the development of CPVT. Recently, a panel of gene curation experts reviewed all published evidence for CPVT-associated genes curated by three independent genes, and identified five more genes with concrete evidence for their causation of CPVT, aside from RyR2 and CASQ2 [ 93 ]. RYR2, CALM1, CALM2, and CALM3 were inherited in an autosomal dominant inheritance, whilst CASQ2, TRDN, and TECRL had an autosomal recessive inheritance [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, although 16 individuals had ANK2 variants that were classified as P/LP, they had similar EHR-derived arrhythmia phenotypes to those with no identified variants, consistent with the fact that the role of ANK2 in several arrhythmia syndromes has recently been disputed. 5,6 Although RYR2 accounted for >25% of the individuals with P/LP variants, none were gainof-function variants that are associated with catecholamine-induced polymorphic ventricular tachycardia, and no enrichment of arrhythmia phenotypes in EHR records was observed. These findings are not unexpected considering the relative rarity of catecholamine-induced polymorphic ventricular tachycardia (1 in 10 000 individuals) and the fact that pathogenic gain-of-function RYR2 variants tend to lead to early-onset disease, whereas the median age of this cohort was 58 years and excluded those with previous indication for cardiac genetic testing.…”
Section: Article See P 877mentioning
confidence: 99%
“…Three other genes ( KCNQ1 , KCNJ2 , SLC4A3 ) presented strong to moderate evidence. Causality of the other SQTS-associated genes remains still in dispute [ 11 ]. These data are consistent with the findings published by Campuzano et al, who found that all variants with a conclusive pathogenic role in SQTS clustered in three genes ( KCNQ1 , KCNH2 and KCNJ2 ).…”
Section: Short Qt Syndromementioning
confidence: 99%
“…Four of them present an AD inheritance pattern ( RYR2 , CALM1 , CALM2 , CALM3 ) and three AR inheritance ( CASQ2 , TRDN , TECRL ). Three genes ( KCNJ2 , PKP2 , SCN5A ) were reported for phenotypes that were not representative of CPVT, while the reported variants in the ANK2 gene were considered too common in the population to be disease-causing ( Table 1 ) [ 11 ].…”
Section: Catecholaminergic Polymorphic Ventricular Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation